Similar periprosthetic joint infection rates after and before a national infection control program: a study of 45,438 primary total knee arthroplasties - Thompson, Olof; W-Dahl, Annette; Lindgren, Viktor; Gordon, Max; Robertsson, Otto; Stefánsdóttir, Anna (Acta Orthopaedica, 2022)
Background and purpose — Strenuous efforts to minimize postoperative infection rates have been made, including the Swedish nationwide initiative Prosthesis Related Infections Shall be Stopped (PRISS). This study calculated the incidence rate of periprosthetic joint infection (PJI) following primary total knee arthroplasty (TKA) before and after PRISS. Patients and methods — All 45,438 primary TKAs registered in the Swedish Knee Arthroplasty Register (SKAR) during 2007–2008 and 2012–2013 were included. Matched data on antibiotic prescriptions were obtained from the Swedish Prescribed Drug Register (SPDR). All patients with ≥ 28 days of continuous antibiotic treatment within 2 years of primary surgery had their medical charts reviewed to identify cases of PJI. The incidence rate was calculated by dividing the number of PJIs by the total time at risk during each time period and presented as percentages with 95% confidence interval (CI). Results — 644 PJIs were identified, equaling a 2-year incidence rate of 1.45% (CI 1.34–1.57). The incidence rate was 1.44% (CI 1.27–1.61) before PRISS and 1.46% (CI 1.31–1.61) after. Diagnosis was made within 30 days of primary TKA in 52%, and within 90 days in 73% of cases. 603 cases were reoperated on or revised. Median time from operation to diagnosis was 29 days (1–716), for both time periods. Debridement with exchange of the insert was performed in 32% and 63% of cases before and after PRISS, respectively. Interpretation — We found similar incidence rates before and after the PRISS initiative without any statistically significant difference. Time to diagnosis was similar during both time periods. The project may have contributed to increased compliance with treatment protocols.